The Role of Fingerprint-Based Forensic Laboratories in Supporting the Disclosure of Firearms Misuse Cases in the North Sumatra Regional Police Area - Yudiatnis; Syawal A. Siregar; Rudolf Silaban (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The Indonesian National Police Forensic Laboratory plays a crucial role in supporting the disclosure of firearms abuse oriented towards firearm fingerprint analysis. Fingerprints on firearms are one of the most important forensic evidence in criminal investigations. In the context of firearms abuse, fingerprints found on weapons can provide critical information about who has held or used the weapon. This study aims to analyze the role of fingerprint-based forensic laboratories in supporting the disclosure of firearms abuse cases in the North Sumatra Regional Police. The research method uses a qualitative method with a normative legal approach, and data collection is done by conducting interviews with laboratory officers, as well as reviewing documents and case reports. The results of this study conclude that fingerprint analysis on firearms, bullets, and cartridges allows for the identification of perpetrators in a scientific and accurate manner. Then, there are several obstacles that affect the role of firearm fingerprint-based forensic laboratories in the North Sumatra Regional Police, namely the challenges in managing evidence that may be damaged or contaminated, as well as the need for technological and technical updates even though the facilities at the North Sumatra Regional Police Bidlabfor are complete. In addition, the lack of coordination between the forensic laboratory and the investigation unit can slow down the examination and analysis process.